The Anzacs at Gallipoli : a story for Anzac day - Pugsley, Christopher (Port Melbourne, Victoria : Lothian Books, 2000)
The day-by-day experiences of Australian soldiers at Gallipoli, told in graphic black and white photographs and text which describes the campaign and includes extracts from soldiers' letters and diaries, boxed information about particular parts of the battlefield, Turkish commanders, weapons, rations, Simpson and his donkey, and more.
1. Remember the Anzacs -- 2. The first Anzac Day, Sunday 25 April 1915 -- 3. Hanging on -- 4. The fields of daisies at Cape Helles -- 5. Quinn's post -- 6. Dying like flies in the summer at Anzac -- 7. Lone Pine, 6-9 August 1915 -- 8. Disaster at the Nek, 7 August 1915 -- 9. The battle for Hill 60 -- 10. Evacuation -- 11. The end.
White
For juvenile.
Keywords: Australia. -- Army. -- Australian and New Zealand Army Corps -- History -- Juvenile literature; World War, 1914-1918 -- Campaigns -- Turkey -- Gallipoli Peninsula -- Personal narratives, Australian; World War, 1914-1918 -- Campaigns -- Turkey -- Gallipoli Peninsula -- Personal narratives, New Zealand; World War, 1914-1918 -- Campaigns -- Turkey -- Gallipoli Peninsula -- Juvenile literature; Australian